2000
DOI: 10.1159/000017500
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo – Coping Behavior

Abstract: Thirty-three inpatients with vitiligo were compared at the Tomesa Klinik (Bad Salzschlirf, Germany) to a healthy control group using the Beck Depression Inventory, Interaction Anxiety Questionnaire (German version: Interaktions-Angst-Fragebogen, Becker), and the Questionnaire on Health Locus on Control Scales (in the German version: Fragebogen zu Kontrollüberzeugungen von Krankheit und Gesundheit – KKG – by Lohaus und Schmitt). The groups were matched for age, sex and social situation. 27.3% of patients attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 15 publications
0
16
1
Order By: Relevance
“…Stress has been implicated for a long time as a trigger or worsening factor in vitiligo [2,12,44]. Several other trigger factors have been suggested, ranging from hormonal changes, exposure to certain chemical compounds and psychological injuries related to stressful life events [12,45].…”
Section: Is There Already Something Different In Patients Before Vitimentioning
confidence: 99%
See 1 more Smart Citation
“…Stress has been implicated for a long time as a trigger or worsening factor in vitiligo [2,12,44]. Several other trigger factors have been suggested, ranging from hormonal changes, exposure to certain chemical compounds and psychological injuries related to stressful life events [12,45].…”
Section: Is There Already Something Different In Patients Before Vitimentioning
confidence: 99%
“…Gieler et al [44] found in 33 patients with vitiligo that the longer they had the disease the less depressed the patients became (assessed with the Beck Depression Inventory; BDI). This finding is not confirmed by the data in Lee et al [55].…”
Section: Has Duration Of Vitiligo Any Influence On Patient's Psycholomentioning
confidence: 99%
“…These include depression, an impaired sense of body image, decreased selfesteem, sexual and relationship difficulties and a general reduction in quality of life Porter et al, 1987;Obermeyer, 1985;Dungey and Busselmeir, 1982]. They also include a reduced sense of control, predictability over one's life and reduced social support [Gieler et al, 2000;Thompson and Kyle, 2000;Picardi et al, 2003]. The visibility of most dermatoses has psychological consequences and can often carry connotations of contagion or a lack of hygiene [Papadopoulos and Walker, 2003;Kleinman, 1988].…”
mentioning
confidence: 99%
“…However, the published results on this topic are not conclusive. Neither Gieler et al (52) nor Lee et al (53) found a difference between patients and controls. Clearly our data are limited because the group that used the BDI after 12 months was too small.…”
Section: Discussionmentioning
confidence: 86%